Rancang Bangun Sistem Informasi Geografis Kuliner Khas Kampar Berbasis Web Sebagai Pendukung UMKM Di Kabupaten Kampar: Rancang Bangun Sistem Informasi Geografis Kuliner Khas Kampar Berbasis Web Sebagai Pendukung UMKM Di Kabupaten Kampar - Zul hamdi islamie; Novi Yona Sidratul Munti; Deddy Gusman (Universitas Pahlawan Tuanku Tambusai, 2022)
Kampar is a district in Riau which has tourism assets that can attract the attention of tourists. The existence of this tourist attraction needs to be supported by the facilities, infrastructure and facilities that support it. However, tourists find it difficult to find culinary locations and typical Kampar foods, due to the unavailability of information. Many tourists also don't know what the typical Kampar dishes are that they can take home and what are the typical Kampar foods. Therefore, tourists need information that can help to find culinary locations and typical Kampar foods. Advances in technology at this time can make it easier to get information quickly and easily. One of them is a geographic information system, a Geographic Information System is a computer-based information system that is used to process and store geographic-based data or information. Utilization of geographic information systems can help find the location of culinary and typical food of Kampar.This study aims to create a web-based geographic information system for Kampar culinary and food using the Google Maps API which makes it easy to find out the location of Kampar culinary and special food, it also provides information to tourists about shop information and what is being sold.